(untitled) ("Conference on Universal Science Research 2023", 2023)
Reading is a multifaceted skill that can permeate all aspects of life. Having strong reading skills allows us to interpret and find meaning in everything we read, and as we continue to improve these skills, we also develop our ability to communicate effectively through writing. This article discusses the development and strengthening of students’ reading skills in English classes.